2008
DOI: 10.1016/j.neuroscience.2007.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase and tensin homolog, deleted on chromosome 10 deficiency in brain causes defects in synaptic structure, transmission and plasticity, and myelination abnormalities

Abstract: The phosphatidylinositol 3-kinase (PI3K) signaling pathway modulates growth, proliferation and cell survival in diverse tissue types and plays specialized roles in the nervous system including influences on neuronal polarity, dendritic branching and synaptic plasticity. The tumor-suppressor phosphatase with tensin homology (PTEN) is the central negative regulator of the PI3K pathway. Germline PTEN mutations result in cancer predisposition, macrocephaly and benign hamartomas in many tissues, including Lhermitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
150
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(175 citation statements)
references
References 64 publications
20
150
2
1
Order By: Relevance
“…Whereas mice used in the present study exhibit ablation of Pten primarily in DGCs and CA3, but not CA1, pyramidal neurons, in the hippocampus, CaMKIIα-Cre Pten and Pten +/− cKO mice exhibit reduced expression of Pten primarily in CA1 pyramidal neurons. Whereas CaMKIIα-Cre Pten cKO exhibit cognitive, but not morphological, abnormalities before their death at ∼11 wk (37), GFAP-Cre Pten cKO and Pten +/− mice exhibit morphological abnormalities, but not cognitive deficits (38)(39)(40). Thus, our findings extend the work of others in that we document deficits in LTP and LTD at DGC synapses in a clinically relevant model of Pten inactivation.…”
Section: Synaptic Plasticity Deficits At Dgc Synapses Precede Morpholsupporting
confidence: 82%
See 1 more Smart Citation
“…Whereas mice used in the present study exhibit ablation of Pten primarily in DGCs and CA3, but not CA1, pyramidal neurons, in the hippocampus, CaMKIIα-Cre Pten and Pten +/− cKO mice exhibit reduced expression of Pten primarily in CA1 pyramidal neurons. Whereas CaMKIIα-Cre Pten cKO exhibit cognitive, but not morphological, abnormalities before their death at ∼11 wk (37), GFAP-Cre Pten cKO and Pten +/− mice exhibit morphological abnormalities, but not cognitive deficits (38)(39)(40). Thus, our findings extend the work of others in that we document deficits in LTP and LTD at DGC synapses in a clinically relevant model of Pten inactivation.…”
Section: Synaptic Plasticity Deficits At Dgc Synapses Precede Morpholsupporting
confidence: 82%
“…Moreover, our observation that marked alterations in synaptic function coincide with and/or precede the onset of behavioral deficits is consistent with the concept of "synaptic failure," postulated to be a causal factor in the dementia associated with Alzheimer's disease (36). Synaptic plasticity deficits have been reported at CA1, but not DGC, synapses of other mouse models of Pten inactivation, including calcium/calmodulin dependent protein kinase II α (CaMKIIα)-Cre Pten cKO mice (37), GFAP-Cre Pten cKO mice (38), and Pten +/− mice (39,40). Whereas mice used in the present study exhibit ablation of Pten primarily in DGCs and CA3, but not CA1, pyramidal neurons, in the hippocampus, CaMKIIα-Cre Pten and Pten +/− cKO mice exhibit reduced expression of Pten primarily in CA1 pyramidal neurons.…”
Section: Synaptic Plasticity Deficits At Dgc Synapses Precede Morpholsupporting
confidence: 68%
“…Indeed, deletion of Pten in multiple neuronal types during development results in profound defects in migration and patterning in brain (Backman et al, 2001;Groszer et al, 2001;Kwon et al, 2001;Marino et al, 2002;Yue et al, 2005). Finally, abnormalities in synaptic structure have been identified in LDD patients, as well as Pten conditional knockout mice (Kwon et al, 2006;Fraser et al, 2008). Thus, the abnormalities observed in LDD can be attributed to key roles of PTEN in neuronal migration, size regulation and specialized subcellular structure.…”
Section: Germline Mutations Of Pten Cause Neurological Abnormalitiesmentioning
confidence: 99%
“…Alternatively, it is possible that individual variation in other regulators of PI3K signaling may cause neurological dysfunction in the context of PTEN haploinsufficiency. Experimental systems have shown that loss of Pten function can have profound consequences on patterning in the brain, proper neuronal morphogenesis and function, as well as defects in myelination (Fraser et al, 2008;van Diepen and Eickholt, 2008), showing remarkably specialized functions for a pathway that is ubiquitously expressed and evolutionarily conserved.…”
Section: Germline Mutations Of Pten Cause Neurological Abnormalitiesmentioning
confidence: 99%
“…Synaptic structures throughout the cortex and cerebellum were enlarged, and axons showed evidence of severe myelin thickening. Loss of PTEN expression also resulted in the development of decreased synaptic functionality, or weakening of both synaptic transmission and synaptic plasticity within the hippocampus [37,38].…”
Section: Autism With Macrocephalymentioning
confidence: 99%